“Canto em qualquer canto”: um estudo sobre voz, trabalho e motivação com cantores populares - Drumond, Lorena Badaró (2011)
This investigation was carried out with 19 male and female singers of different generations, attempting to broaden the knowledge on aspects of their trajectories and their work: insertion into music, difficulties in personal and professional quotidian life, career plans, working conditions, voice and vocal health care practices. The participants were interviewed and answered a questionnaire with questions of speech-language pathology interest. An in loco evaluation of the environment where a show of each singer occurred was performed. The results were organized and interpreted using the classical content analysis technique. The interest on the activity was early and related with the existence of a musical family environment. The interest on popular singing developed in association of learning to play a musical instrument. The interviewees pointed out several difficulties on professional daily life, but also related situations of great satisfaction, suggesting a quotidian marked by ambiguity. A significant part of the singers do not live on singing alone. Technical vocal preparation was not highlighted as a significant aspect. General health habits and vocal health habits, as well as preventive care, showed themselves to be insufficient. Half of the singers reported voice related complaints. The most frequent show venues were open drinking bars with no acoustic preparation for live music. The participants survive in a precarious regulation context, which does not assure good conditions of work, health, or pay. Nevertheless, life in situations of satisfaction and recognition, as well as the possibility of fame, contribute to the motivation of pursuing the career.